Using Cover Crops as an IPM Tool for Managing Hard‐to‐Control Weeds. Issue 2 (3rd March 2021) - Proctor, Chris
Abstract: While herbicides provided an opportunity to expand many important soil conservation practices, overuse of glyphosate and the evolution of glyphosate‐resistant weeds poses one the greatest threats to conservation tillage as it has forced some farmers to revert to conventional tillage for effective weed control. Cover crops have the potential to delay weed emergence, decrease weed size, and decrease weed number. However, the beneficial gains in cover crop–related weed suppression should be considered against the potential trade‐offs with cropping system productivity. This article is the first in the three‐part series in Crops & Soils magazine. It is part of an American Society of Agronomy training series sponsored by the Kellogg Company. Earn 0.5 CEUs in Integrated Pest Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/941 .